Anti-inflammatory and antinociceptive activity of urera aurantiaca - Riedel, Rodrigo Nicolas (2014)
Urera aurantiaca Wedd. (Urticaceae) is a medicinal plant commonly used in traditional medicine to relieve pain in inflammatory processes. In the present study, the in vivo anti-inflammatory and antinociceptive effects of U. aurantiaca methanolic extract and its possible mechanisms of action were investigated. The extract showed anti-inflammatory activity in the ear edema in mice test (34.3% inhibition), myeloperoxidase (MPO) activity was markedly reduced in animals administered with the extract: within 49.6% and 68.5%. In the histological analysis, intense dermal edema and intense cellular infiltration of inflammatory cells were markedly reduced in the ear tissue of the animals treated with the extract. In the carrageenan-induced hind paw edema in rats assay the extract provoked a significant inhibition of the inflammation (45.5%, 5 h after the treatment) and the MPO activity was markedly reduced (maximum inhibition 71.7%), The extract also exhibited significant and dose-dependent inhibitory effect on the increased vascular permeability induced by acetic acid. The extract presented antioxidant activity in both 2,2-diphenyl-1-picrylhydrazyl and 2,2′-azinobis 3-ethylbenzothiazoline 6-sulfonic acid tests and its total phenol content was 35.4 ± 0.06 mg GAE/g of extract. Also, the extract produced significant inhibition on nociception induced by acetic acid (ED50: 8.7 mg/kg, i.p.) administered intraperitoneally and orally. Naloxone significantly prevented this activity.